Cell cycle control of Notch signaling and the functional regionalization of the neuroepithelium during vertebrate neurogenesis - Latasa, Maria Jesus; Cisneros, Elsa; Frade, Jose Maria (The International journal of developmental biology, 2009)
A critical feature of vertebrate neural precursors is the to-and-fro displacement of their nuclei as cell cycle progresses, thus giving rise to a pseudostratified epithelium. This nuclear behavior, referred to as interkinetic nuclear migration (INM), is translated into the disposition of the cell somas at different orthogonal levels depending on the cell cycle stage they are. The finding that important regulators of neurogenesis, such as the proneural and neurogenic genes, undergo cyclic changes of expression and function in coordination with the cell cycle and the INM, and that the neurogenic process correlates with a particular window of the cell cycle, in coincidence with the apical localization in the neuroepithelium of neural precursors, is a novel concept that facilitates our understanding of the neurogenic process in vertebrates. As such, recent data support the notion that the three-dimensional structure of the neuroepithelium is crucial for proper neuronal production. In this review, we describe current knowledge of the molecular mechanisms involved in the differential expression and function of the proneural and neurogenic gene products along the cell cycle, and we discuss important consequences for vertebrate neurogenesis derived from this observation.